(Table 1) Composition of basal sediments collected at DSDP Holes 59-449 and 59-450 - Martha R Scott; George W Bolger (PANGAEA, 1981)
This chapter addresses the question of whether backarc spreading centers leave the same fingerprint of metal-enriched sediments that mid-ocean ridge spreading centers are so well known to leave. DSDP Legs 59 and 60 made an east-west traverse across the South Philippine Sea. Samples were collected in the Parece Vela Basin (Sites 449 and 450), the West Mariana Ridge (Site 451), and the Mariana Trough (Sites 452-460). No samples from the West Philippine Basin were analyzed, because original basal sediments had been eroded and replaced with coarse volcaniclastic breccia derived from the igneous basement itself (see Site 447 report, this volume). We analyzed basal-sediment samples from Holes 449 and 450 in the Parece Vela Basin (Leg 59) and from Holes 453, 459B, and 460A (Leg 60) for aluminum, calcium, magnesium, total iron, manganese, copper, colbalt, and nickel. Data and discussion of the results of Leg 59 are included in this report; those for Leg 60 are forthcoming in that volume.
Supplement to: Scott, MR; Bolger, GW (1981): Metallogenesis in the Parece Vela Marginal Basin complex of the Philippine Sea, Deep Sea Drilling Project Leg 59. In: Kroenke, L; Scott, R; et al. (eds.), Initial Reports of the Deep Sea Drilling Project (U.S. Govt. Printing Office), 59, 649-652, https://doi.org/10.2973/dsdp.proc.59.127.1981